2014
DOI: 10.3354/dao02704
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoimmunopathologic findings in Atlantic bottlenose dolphins Tursiops truncatus with positive Chlamydiaceae antibody titers

Abstract: Sera from free-ranging Atlantic bottlenose dolphins Tursiops truncatus inhabiting the Indian River Lagoon (IRL), Florida, and coastal waters of Charleston (CHS), South Carolina, USA, were tested for antibodies to Chlamydiaceae as part of a multidisciplinary study of individual and population health. A suite of clinicoimmunopathologic variables was evaluated in Chlamydiaceae-seropositive dolphins (n = 43) and seronegative healthy dolphins (n = 83). Fibrinogen, lactate dehydrogenase, amylase, and absolute number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In this study, the seroprevalence of C. psittaci was 85 and 84% in dolphins from the IRL and CHS, respectively. Our follow-up study demonstrated that dolphins with a seropositive Chlamydiaceae antibody titer had several immunologic irregularities when compared to healthy dolphins (Bossart et al 2014). Dolphins with positive Chlamydiaceae titers had significantly lower Con A-induced T lymphocyte proliferation, LPSinduced B lymphocyte proliferation, and granulocytic phagocytosis when compared to healthy dolphins.…”
Section: Chlamydiaceaementioning
confidence: 74%
See 2 more Smart Citations
“…In this study, the seroprevalence of C. psittaci was 85 and 84% in dolphins from the IRL and CHS, respectively. Our follow-up study demonstrated that dolphins with a seropositive Chlamydiaceae antibody titer had several immunologic irregularities when compared to healthy dolphins (Bossart et al 2014). Dolphins with positive Chlamydiaceae titers had significantly lower Con A-induced T lymphocyte proliferation, LPSinduced B lymphocyte proliferation, and granulocytic phagocytosis when compared to healthy dolphins.…”
Section: Chlamydiaceaementioning
confidence: 74%
“…Both E. rhusiopathiae and C. psittaci infections have been described in marine birds (Hubálek 2004). We speculated that the high seroprevalence of antibody to both Chlamydiaceae and E. rhusiopathiae in HERA dolphins might be caused by shedding of the agents among local bird reservoir populations which in turn may serve as potential sources of both chlamydial and E. rhusiopathiae infection (Bossart et al 2014). The data suggest inapparent Chlamydiaceae infection impacts immunologic status which could make infected IRL and CHS dolphins susceptible to other diseases.…”
Section: Chlamydiaceaementioning
confidence: 94%
See 1 more Smart Citation
“…Groundwaters contaminated by OSTDS have impacted a wide variety of other urbanized estuaries and coastal waters, including Bermuda (Lapointe and O'Connell, 1989;McGlathery, 1995), the Florida Keys (Lapointe et al, 1990;Tomasko and Lapointe, 1991;Lapointe et al, 1994), Cape Cod, MA (Valiela et al, 1992;Weiskel and Howes, 1992;Valiela et al, 1997), Outer Banks, North Carolina (Mallin, 2013), Chesapeake Bay (Reay, 2004), and Puerto Rico (Olsen et al, 2010). In addition, bacterial contamination of groundwaters and surface waters has been associated with unsuitable soil characteristics and high densities of OSTDS on the IRL watersheds (Lapointe and Krupa, 1995a,b;Belanger et al, 2007;Lapointe et al, 2012) and is considered a primary source of bacterial contamination associated with immunologic perturbations in populations of bottlenose dolphins, Tursiops truncatus Montagu, in the IRL (Schaefer et al, 2009;Bossart et al, 2014). Schaefer et al (2011) found a positive correlation between the number of IRL bottlenose dolphins colonized by Escherichia coli and the number of septic tanks in the area they lived; with the highest number of both being in the northern segments of the IRL.…”
mentioning
confidence: 99%
“…For example, dolphins infected with lobomycosis, a mycotic skin disease, displayed a suppressed immune system compared to dolphins without a visible infection [19]. Dolphins with antibody titers positive to bacterial infection, Chlamydiaceae , showed changes in their innate and adaptive immunological parameters [20]. Dolphins with positive morbilliviral antibody titers had decreased T cell proliferation and absolute number, suggestive of adverse changes in their immune system [21].…”
Section: Introductionmentioning
confidence: 99%